Evacuation Training of Teacher and Student Actions in Disaster Risk Management at Abdul Qadir Paud - Surya Utama; Balqis Nurmauli Damanik; Hely Hely; Syahferi Anwar; Annisatun Munawarah (STIKES Columbia Asia Medan, 2025)
Teachers have a key role in ensuring the safety of students during disasters, however, to carry out this role effectively, they need a deep understanding of disaster inclusive risk reduction education. Early age students are the group most at risk in disasters. Inclusive disaster preparedness education training for teachers aims to increase teacher competence in designing inclusive learning programs related to disaster preparedness in schools. Through participatory methods with an andragogy approach, teachers are trained to develop individual learning programs and develop learning tools that are responsive to students' needs. The training also includes the preparation of inclusive earthquake simulation scenarios, where participants learn to design safe and accessible evacuation routes and respond to various types of student needs. The results of this activity show a significant increase in teachers' understanding and skills regarding inclusive disaster preparedness, as evidenced by the learning tool products produced during the training. The importance of continuous training and collaboration with various stakeholders to strengthen disaster preparedness in schools